Introduction to Focus Issue on Laudato Si' - Jenkins, Willis (Journal of religious ethics, 2018)
The encyclical Laudato si' can be read as a religious ethic in several different ways. Contributors to this focus issue read it as magisterial teaching, as environmental thought, as Global South criticism, as Latinx theology, and as philosophy of religion. Foregrounding South American and Latinx receptions, the cumulative argument of this focus issue is that LS represents a cultural event that invites interpretations from contexts and disciplines beyond North Atlantic theological ethics.